Pengaruh Perputaran Modal, Leverage dan Likuiditas terhadap Profitabilitas dengan Ukuran Perusahaan sebagai Variabel Moderasi Perusahaan Yang Terdaftar Pada JII 70 Tahun 2020-2022 - Aryani, Putri; Budi Santoso, Suryo; Hariyanto, Eko; Kusbandiyah, Ani (Jurnal Ecogen, 2024)
This research aims to determine the effect of capital turnover, leverage, liquidity on profitability with company size as a moderating variable. The population of this research are companies listed on the Jakarta Islamic Index for the 2020-2022 period. This research is quantitative research. Sample selection used a purposive sampling technique, with predetermined criteria a sample of 159 companies registered on the Jakarta Islamic Index 70 was successfully obtained. The data analysis method in this research used the Classical Assumption Test and Moderated Regression Analysis (MRA). So the results of this research state that turnover capital has a significant positive effect on profitability, on average it has a significant negative effect on profitability, liquidity has a significant positive effect on profitability, company size has a significant negative effect on profitability and company size is able to moderate the effect of liquidity on profitability